(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The surface ultrastructure of seeds coat of the genus Gladiolus L. of the Ukrainian flora was examined. The studied seeds of genus Gladiolus species of the flora of Ukraine are characterized both common and distinct features. The common features are shape and position of cicatricle (rectangular, small, by position – basal), type of cuticle (wrinkled, well developed in all investigated seeds), form and limits of cells of test (polygonal, their boundaries are clearly visible), anticlinal cell walls (uniformly thickened, straight). These features, we suggest, could be additional diagnostic at the genera level. The distinct characteristics are seeds shape, the presence and position of the wing, the level of periclinal cell walls of seed coat, and the type of relief. We suppose these characteristics are additional diagnostic at the species level on which basis we propose the key to determine the species of the genus Gladiolus.